Fatores determinantes de adoção de sistemas de integração lavoura-pecuária-floresta no estado de São Paulo - Bernardo, Roberto (Universidade Federal de São Carlos, 2020)
Agribusiness has contributed to the trade balance surplus and has been fundamental in the growth of the Brazilian Gross Domestic Product (GDP). However, the major challenge for agribusiness is to increase agricultural production and at the same time conserve the natural resources involved. Concern for a more sustainable rural production in the economic, social and environmental perspectives has been the focus of many discussions. Production systems that integrate livestock and crop, including tree components, have been suggested as a sustainable option. Even though it is a relatively familiar alternative for cattle ranchers, the adoption of these systems is still low. The specific and distinct way in which ranchers use their resources and their capacities are suggested as possible determinants of the adoption and diffusion of new technologies. However, there are still few analyzes about these determinants for the adoption of integration systems, especially through the approach of resource-based vision and ordinary and dynamic capabilities. Given this context, the following question is presented as the research problem: what are the determining factors for the adoption of integration systems with agricultural, livestock and forestry activities in the state of São Paulo? Therefore, the objective is to identify the determining factors for the adoption of these systems in the state of São Paulo locus. The research started from the literature review that allowed to build a conceptual model, whose main axis is composed by the characteristics of the producers and the rural properties. The literature review, theoretical and empirical, also allowed the identification of the main determinants and their variables, essential for the formulation of the hypotheses to be tested. In the second stage of the research, a field research was applied in a sample of 175 rural producers adopters and non-adopters of the integration systems. The results obtained from the analyses allowed us to identify that the adoption of integration systems depends on the objectives and strategic choices of the rural producers. The resource-based view, through the characterization of rural properties, has allowed us to identify available resources, physical and human, relating them to the decision of producers to adopt integration systems. Through the characteristics of farmers, we realized that the decision to adopt or not a new technology can be determined by factors such as producer profile, which encompasses education, experience, skills and abilities. The results obtained from descriptive and multiple correspondence analyzes and multinomial logistic regression, indicate that Integrated crop-livestock system adopters have properties with flat land, areas greater than 300 hectares, greater numbers of tractors and planting equipment, herds greater than 330 heads, greater availability of labor and are located close to the market, grain drying and storage services. They have characteristics of greater experience with agriculture, greater participation in cooperatives and technical events and receive more technical visits. Integrated Livestock-Forest system adopters, on the other hand, have properties with more sloping, smaller land, less machinery and labor, are located far from the market and grain drying and storage services. In addition, they have less experience with agriculture, less participation in cooperatives and technical events and receive less technical visits. These results can contribute to a better understanding of the adoption and diffusion of new technologies in the field and, consequently, collaborate for regional development and for productive sustainability.
Determinant factors of adoption of crop-livestock-forest integration systems in the state of São Paulo
Keywords: Adoção de tecnologia agrícola; Visão baseada em recursos; Capacidade ordinária e dinâmica; Produção pecuária bovina.; Adoption of agricultural technology; Resource-based-vision; Ordinary and dynamic capacities; Bovine livestock production; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA